ANALISIS LAPORAN KEUANGAN PERIODE 2022-2024 PADA PT SUPRA BOGA LESTARI TBK JAKARTA - Alya Shahira; Enggun Gunawan (POLITEKNIK LP3I JAKARTA, 2026)
This study was conducted to evaluate the company’s ability to manage financial resources and ensure business sustainability. The methodology used was a quantitative descriptive approach based on an analysis of officially published annual financial statements. The results indicate that the company’s financial performance has improved, particularly in 2024. Regarding liquidity, the current ratio, quick ratio, and cash ratio have not yet demonstrated optimal capacity to meet short-term obligations. From a solvency perspective, there has been a decline in the debt to assets ratio, debt to equity ratio, and long term debt to equity ratio, indicating an improvement in capital structure. Meanwhile, regarding profitability, the gross profit margin, net profit margin, return on assets, and return on equity ratio have improved, with net income shifting from a negative position in 2022-2023 to a positive one in 2024. Overall, it can be concluded that there has been a recovery in the financial performance of PT Supra Boga Lestari Tbk. However, the company still needs to improve its liquidity management and strengthen its capital structure.